Pajak Naik, Beban Rakyat Menukik - Ety Isworo (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The government plans to increase the Value Added Tax (VAT) rate by 1%, from 11% to 12% in 2025. This policy has certainly triggered various reactions in society, from support to concern, especially regarding its impact on the prices of basic necessities and people's purchasing power. Value Added Tax (VAT) is a tax levied on the consumption of goods and services within the Customs Area, imposed at each stage of production and distribution. VAT collected by the central government applies to the purchase and sale of certain goods and services, such as motor vehicles, houses, and internet services, which will be subject to the 12% VAT rate. The Minister of Finance emphasized that the increase in VAT rates does not apply to people's basic needs. Basic necessities, as well as critical services like healthcare and public education, will remain exempt from VAT or will be subject to lower rates. Secretary of the Coordinating Ministry for Economic Affairs, Susiwijono Moegiarso, said that the technical details of implementing 12 percent VAT will be contained in the Minister of Finance Regulation (PMK) which is currently being drafted by the Ministry of Finance (Kemenkeu). Will this policy become an obstacle to national economic growth, especially in the public purchasing power sector? What are the impacts on purchasing power, the business world and economic recovery? What are the government's steps to reduce the negative impacts of this policy